Chronic liver disease in patients with Schizophrenia: a review - Zaini, Syahrir; Ahmad, Nurul Aini (Malaysian Psychiatric Association, 2018)
: Schizophrenia is a chronic psychotic disorder characterised by severely impaired behaviors, thinking, and emotion. Patients with schizophrenia are closely related to chronic liver disease. The prevalence of chronic liver disease in patients with schizophrenia (7.0%) was 1.27 times as high as that of the general population (6.1%). This is due to many reasons such as metabolic syndrome, effects of antipsychotic drugs, alcohol consumption and smoking. Objectives: The objectives of this review paper are to discuss about the common terms related to chronic liver disease and the relationship between chronic liver disease and schizophrenia. Discussion: Chronic liver disease is divided into few types like non-alcoholic fatty liver disease, hepatitis, cirrhosis and many more. The types depend on the aetiology of the disease. There are specific mechanisms on how the schizophrenia and chronic liver disease are related to each other. Conclusion: In conclusion, metabolic syndrome, the usage of antipsychotics drug, alcohol consumption and smoking are the main factors that can lead to chronic liver disease in schizophrenia patients. It is important to make all people related with this disorder to understand the mechanism, which may help schizophrenia patients to prevent from the liver disease.